IbM Gerakan Cuci Tangan (CITA) sebagai Upaya Pencegahan Terjadinya Diare pada Anak Prasekolah - Fitri Wahyuni; Yuni Astuti (Lembaga Pengembangan Kinerja Dosen, 2025)
Diarrhea remains one of the leading causes of morbidity and mortality among children under five, including in Indonesia. Preschoolers are particularly vulnerable due to their immature immune systems and frequent contact with the environment during play. Poor hygiene practices, especially the lack of proper handwashing with soap, are major contributing factors. This community service program aimed to improve preschool children’s knowledge and skills in handwashing through the Handwashing Movement (CITA) at TK Kartika III-10 Semarang on April 17, 2025, involving 34 students and 3 teachers. The intervention included health education, educational videos, ice breaking activities, and demonstration of the WHO-recommended six steps of handwashing, followed by guided practice. Evaluation results showed a significant improvement in correct handwashing skills, increasing from 24% before the intervention to 88% after. The CITA program proved effective in fostering handwashing habits among preschoolers and has the potential to reduce the incidence of diarrhea while promoting healthy living from an early age.